Presenting the model of social entrepreneurship in the development of rural tourism in the target villages of Gilan province - Fatemeh Doozandeh Ziabari; hamed fallah tafti; Mir Mohammad Asadi; Mahdi Basouli (ارزش آفرینی در مدیریت کسب و کار)
The purpose of this research is to provide a model of social entrepreneurship in the development of rural tourism in the target villages of Gilan province. The research method is qualitative and applicable. The statistical population of the research includes 10 managers, experts and university professors in the field of tourism, selected by purposeful sampling and inviting interviewees. The results of the qualitative questionnaire and open interview with the sample members, after taking notes and transferring to the system, were analyzed using coding and the data-based method and Maxqda software, and the output and the final model were reported. The results showed that traditional tourism entrepreneurship follows a capitalist approach, is highly profit-oriented, and ignores the social aspects of doing business; which may in turn cause more harm to already disadvantaged communities. Social entrepreneurship in tourism, referred to here as tourism social entrepreneurship, is positioned as a market-oriented approach to address various social problems through tourism entrepreneurship.Extended Abstract                                           IntroductionTourism entrepreneurship is a popular research topic due to its ability to combine different topics such as technological innovation, economic geography, and cultural change. In general, it includes the use of innovation, risk-taking, and being active in a tourism environment (Ratten, 2020). Social entrepreneurship refers to innovations, new business ventures, and models as strong business objectives. On the other hand, social entrepreneurship is more ethical in entrepreneurial activities, with a detailed social change plan, influenced by social and environmental values ​​(Branzei, 2012; Haugh & Talwar, 2016). This is due to the drastic changes caused by technology innovation; like entrepreneurship through the sharing economy, which leads to direct interaction of people with tourism services (Yu & Wang, 2019). This emphasis on technology in tourism entrepreneurship is important because new innovations are constantly changing industry dynamics (Yu & Spencer, 2021; Buhalis et al, 2019). Since entrepreneurship is a broad field in general, there are many opportunities for researchers in this field to focus on areas of interest which have been neglected (Fu et al, 2019). The phenomenon of social entrepreneurship in the development of rural tourism has been raised as a critical issue in the field of improvement and welfare of communities. Instead of maximizing profit, it focuses on social problems; because it brings local social benefits such as cultural integration and employment (Celebi et al, 2020).Considering the importance of social entrepreneurship criteria and the lack of studies in the field of examining these criteria to achieve development goals, the purpose of this research is to identify social entrepreneurship criteria in the development of tourism in rural areas in Gilan province. Therefore, in this research, the researcher intends to answer the basic question that what the model of social entrepreneurship in the development of rural tourism in the target villages of Gilan Province is.Theoretical FrameworkRural entrepreneurshipRural entrepreneurship is an activity that helps rural people to turn opportunities into profitable economic activities and provides employment, increased income and wealth production, improves the quality of life, and helps local people to participate in the economy (Reagan, 2002).Entrepreneurship and tourismThe creative use of the concept of entrepreneurship for community-based tourism is known as an approach to improve the quality of life of communities as well as provide livelihood and sustainable development (Tan et al, 2018). The most important advantage of promoting entrepreneurship in tourism can be said that since the tourism sector is one of the country's economic sectors and in fact, one of the axes of the country's economic development, thinkers and policy makers have paid special attention to the development of entrepreneurship in tourism and solving its problems (Hesam et al, 2015).Tourism social entrepreneurshipSheldon et al, (2017) have defined the tourism social entrepreneurship as follows: a process that uses tourism to create innovative solutions for urgent social, environmental and economic problems in the destination by mobilizing ideas, capacities, resources and social agreements, from inside or outside the destination, for its sustainable social transformation (Sheldon et al, 2017).Mansoori et al, (2024) investigated the presentation of the model of factors affecting the development of scientific tourism in Iran's higher education system. The obtained results showed that the nine main factors affecting the formation of higher education tourism in Iran in order of influence are: dynamic political exchanges with the world at the national level, the existence of macro-national policies in the field of academic interaction, facilitating the process of acceptance in political and administrative dimensions, the existence of economic and technical infrastructures for foreign students, the international language level of faculty members and staff as well as the structure of dynamic and accepting higher education, the existence of a sense of security in social, security and political dimensions for foreign students, and branding factors of universities and introducing historical, cultural and religious attractions to the world.Ratten (2020) in a research comprehensively examined researches in the field of entrepreneurship in tourism and it is noted that it focused on lifestyle and sustainable forms of tourism entrepreneurship without considering emerging technologies and other forms of entrepreneurship like digital and social.Research methodologyThe research method is qualitative and applicable. The statistical population of the research includes 10 managers, experts and university professors in the field of tourism, selected by purposeful sampling and inviting interviewees.Research findingsThe results of the qualitative questionnaire and open interview with the sample members, after taking notes and transferring to the system, were analyzed using coding and the data-based method and Maxqda software, and the output and the final model were reported. The results showed that traditional tourism entrepreneurship follows a capitalist approach, is highly profit-oriented, and ignores the social aspects of doing business; which may in turn cause more harm to already disadvantaged communities. Social entrepreneurship in tourism, referred to here as tourism social entrepreneurship, is positioned as a market-oriented approach to address various social problems through tourism entrepreneurship.ConclusionThe present study was conducted with the aim of providing a model of social entrepreneurship in the development of rural tourism in the target villages of Gilan province. The results of this research are aligned with the results of Mansoori et al, (2024), Yahya Zadeh et al, (2023), Vukovic et al, (2023), Falah Tafti et al, (2023), Buruj Ali (2022), Ratten (2020), Meitriana et al, (2019), Aquino et al, (2018), Mahmoudzadeh & Arjamandian (2016), Hesam et al, (2015), and Roknodin Eftekhari et al, (2013). Fallah Tafti et al, (2023) introduced two criteria of belief in entrepreneurship and creative use of resources at the ninth level at the end of the model specified in their research, as the most effective criteria affecting other criteria.Considering the importance of the categories of technological factors and innovation in the development of tourism, it is suggested to create disruption in the traditional tourism industry, rely on the aspect of continuity of innovation in it, which is an inseparable aspect of social entrepreneurship. On the other hand, in order for tourism destinations to be able to create a competitive advantage, businesses related to local tourism should follow the model of social businesses that use innovative strategies related to the provision of products and services, organizational structure, operational processes, procurement and marketing.